Extraviando imagens em um percurso autoformativo - Araújo, Marcos Felipe Fidelis (2024)
This dissertation sets out to think about how visualities guide the formation of subjects and, consequently, the implications they have for their understanding of themselves. By visuality I mean the constructed ways of looking or the culture of seeing apprehended in its social and historical context, which enables certain ways of seeing ourselves and weaving self-images from these conceptions. I place myself as the subject of this autobiographical investigation, with the aim of reviewing my training process together with the images that represent the authorized ways of seeing that were given to me from my experience as an EXTRAviada child, who understands himself as a young gay man in a homophobic society, based mainly on religious beliefs. The concept of misplacing images arose from the appropriation of the work by artist Bento Ben Leite entitled “Born to ahazar” (2013), which was censored at the exhibition Queer Museum: cartographies of difference in Brazilian art in 2017, which propagated the concept of the queer child. Based on contributions from the field of visual culture studies, I sought to understand the role of images as devices that help in the process of understanding the subject about their life trajectory. I find in artistic practice a self-formative potential that throughout history has enabled various subjects to claim the autonomy of their gaze on themselves, unleashing a self-creative process that is also self-formative, which according to Pineau (2014) consists of "becoming an object of formation for itself" (p.95). Faced with the impossibility of conceiving of myself as a subject based on the identities that have been offered to me, I try to create my own references, going beyond the meanings of the images that have (con)formed me into a distorted and limited perspective of who I could be. Through artistic practice, I reflect on my formative journeys as a subject, returning to the path of creating a character called Mimimon that I developed during the initial years of my undergraduate degree in Visual Arts, which records my formative journey in relation to the images that guided my formation, from which I intend to question my experiences and understand the constitution of the gaze on myself. The image of this character, which is close to the conception of the Devil that I acquired in childhood, is seen as a counter-visuality that authorizes me to claim my formative power to confront the beliefs that have restricted my gaze. In the end, I realize that the dissertation has become a space for formative and methodological experimentation that helps critical reflection on the construction of the subject's own gaze, supported by the images that contributed to his formation, appropriating the Biographical Project Workshop (Delory-Momberger, 2006) to propose the Autobiographical Visual Narratives Workshop, process in which I have immersed myself throughout the research as research method of investigation and the main contribution of this dissertation to the field I’m inserted.